Pneumococcal colonization among tracheostomy tube dependent children - (:unkn) unknown (PUBLIC LIBRARY SCIENCE, 2018)
Streptococcus pneumoniae colonization is a precursor to pneumococcal disease. Although children with a tracheostomy have an increased risk of pneumococcal pneumonia, the pneumococci colonizing their lower airways remain largely uncharacterized. We sought to compare lower respiratory tract isolates colonizing tracheostomy patients and a convenience sample of isolates from individuals intubated for acute conditions. We collected pneumococcal isolates from the lower respiratory tract of 27 patients with a tracheostomy and 42 patients intubated for acute conditions. We compared the penicillin susceptibility, rates of co-colonization, genetic background, and serotype of isolates colonizing these patient populations. Isolates from both groups showed high genetic diversity. Forty multi-locus sequence types and 20 serotypes were identified. There was no significant difference in serotype distribution, co-colonization rates, vaccine coverage, or non-susceptibility to penicillin among pneumococcal isolates from the two groups. Colonization of the lower airways with non-vaccine serotypes 15B/C, 23B and 35B was noted for the first time in patients with tracheostomies and supports recently observed increases in nasopharyngeal colonization and disease due to these serotypes.
Keywords: STREPTOCOCCUS-PNEUMONIAE; UNITED-STATES; SEROTYPE 35B; DISEASE; RISK